Teacher Strategies in Improving the Quality of Learning in the Era of Disruption in Early Childhood Institutions - Khusnia, Latifa; Formen, Ali (Jurusan PGPAUD FIP UNNES, 2022)
The rise of news about crimes of sexual violence in early childhood has resulted in the number of sexual violence in Indonesia increasing drastically every year. This can be seen from the KemenPPPA data which states that sexual violence experienced by children in Indonesia reaches a percentage of 45.08%. This study aims to determine the concept of sexuality education in UNNES Labschool Kindergarten and the integration of sexuality education in UNNES Labschool Kindergarten. This study used a qualitative research method with a case study approach at the UNNES Labschool Kindergarten. Data collection techniques were carried out by interviews, observation and documentation. Methods of data analysis using descriptive analysis. The results of this study indicate that the concept of sexuality education starts from identifying children's self-identities until children know how to protect themselves from attempts at sexual violence. And basically children already know their own identity and are able to protect themselves from attempts at sexual violence. Parents have hope that in the future there will be an association or organization that can deal with sexual violence against children. Actually, sex education and sexuality education have different meanings.